2007
DOI: 10.1292/jvms.69.531
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Proliferation and Lungworm (Stenurus ovatus) in a Bottlenose Dolphin (Tursiops turncatus)

Abstract: ABSTRACT. A female adult bottlenose dolphin suddenly died at 17 days after the capture. Macroscopically, severe pulmonary congestive edema was found. Histopathology revealed many lungworms in the bronchioli and the worms were identified as Stenurus ovatus. Variously sized vessels proliferated around the lesioned bronchioli. Based on these findings, chronic bronchopneumonia due to the lungworm was diagnosed and vascular proliferation was similar to angiomatosis recently reported in Atlantic bottlenose dolphin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
1
11
1
Order By: Relevance
“…These results are in contrast to studies of the harbor porpoise in which the number of lung nematodes did not differ between young and old animals (Balbuena et al, 1994). Other studies have shown that young odontocetes are infected with lung nematodes (Woodward et al, 1969;Balbuena et al, 1994;Parsons et al, 1999;Parsons and Jefferson, 2000;Kuramochi et al, 2000;Bossart et al, 2003;Kuwamura et al, 2007;Stockin et al, 2009), raising the question of how the parasites are transmitted. Three possibilities have been suggested: 1) via the placenta, 2) via the milk, and 3) via an intermediate host as a prey species.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…These results are in contrast to studies of the harbor porpoise in which the number of lung nematodes did not differ between young and old animals (Balbuena et al, 1994). Other studies have shown that young odontocetes are infected with lung nematodes (Woodward et al, 1969;Balbuena et al, 1994;Parsons et al, 1999;Parsons and Jefferson, 2000;Kuramochi et al, 2000;Bossart et al, 2003;Kuwamura et al, 2007;Stockin et al, 2009), raising the question of how the parasites are transmitted. Three possibilities have been suggested: 1) via the placenta, 2) via the milk, and 3) via an intermediate host as a prey species.…”
Section: Discussioncontrasting
confidence: 67%
“…Those reported from common bottlenose dolphins include Stenurus spp. from Japan (Kuwamura et al, 2007) and the Black Sea (Tsocheva et al, 1992); Halocercus spp. (including H. lagenorhynchi) from South Australia (Johnston and Mawson, 1941), the Black Sea (Tsocheva et al, 1992), and Florida (Dailey et al, 1991); and Pseudalius inflexus from the Black Sea (Tsocheva et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that parasite-dependent severe inner ear infections may cause dysregulation in hearing and navigation abilities [21] . Although some parasitic larvae were also seen in alveoli in the case of S. minor, not detecting any chronic lesion or adult parasite sections was interpreted as a sign of early infection in this case [14][15][16]19] .…”
Section: Discussionmentioning
confidence: 96%
“…In one study, the prevalence of lungworm infections was determined to be 77% in the stranded bottlenose dolphins [15] . To date, Stenurus ovatus, Halocercus lagenorhynchi, Pharurus alatus, and Skrjabinalius cryptocephalus related verminous pneumonia [1,15,16] was reported in the bottlenose dolphins; but there was no case related to S. minor. It is reported that the prevalence of S. minor infection of harbor dolphins on the coast of Norway, Iceland, Greenland and South America was 66-100% [17,18] .…”
Section: Discussionmentioning
confidence: 98%